Model MSN Approach dalam Implementasi Kebijakan Pengelolaan Sampah - Abror, M. Daimul; Probojati, Rasyadan Taufiq (Universitas Dr. Soetomo Surabaya, 2023)
This study aims to analyze, describe and interpret the implementation of waste management in Nganjuk Regency with a focus on the perspectives of Mentality-Approach, Systems-Approach, and Networking-Approach. Data collection uses four main instruments including observation, interviews, FGD, and documentation. Data analysis uses an interactive data analysis model developed by Miles, Huberman, and Saldana. The results showed that in the mentality approach aspect aspects of behavior, attitudes and responsibilities of the government apparatus (DLH, District and Kelurahan Government) regarding waste management in the Nganjuk sub-district have led to a caring attitude about the importance of keeping the environment clean, responsible behavior by overseeing and educating the public regarding waste management using the 3R method (reduce, recycle, re-use). Meanwhile, from the side of the residents, various facts were found related to the enactment of this regional regulation on waste management. Whereas the system approach aspect shows the fact that the implementation of the Waste Management policy in Nganjuk District is quite clear in the regulatory aspect referring to the Nganjuk PERDA number 01 of 2015. Meanwhile the networking approach aspect shows the fact that strategic partnerships in the implementation of the waste management policy are seen in the meeting point of interests between the district government through DLH, the sub-district government through the existing sub-districts and the community through the existence of waste banks scattered throughout the villages in the Nganjuk sub-district. Although it has not shown maximum mutualism synergy and symbiosis.